A data-hiding scheme based on one-way hash function. (16th December 2010) - Chang, Chin-Chen; Lee, Chia-Yin; Chen, Chang-Chu; Wang, Zhi-Hui
Data hiding in digital images is a useful technique to embed secret information into a host image. In this article, we employ the one-way hash function to present a new data-hiding scheme in the VQ-compressed domain. In order to extend the hiding capacity for the proposed scheme, we use the concept of SMVQ to increase the embeddable indices of the VQ-index table. Moreover, our experiments show that proposed method has a larger hiding capacity than other related works.